Coupled electro-thermal transmission line modelling (TLM) method - Elkalsh, Ahmed (2017)
The theme of this thesis is concerned with the modelling of the multi-physics interactions that occur in lightning and arc discharge. The main contributions of this research are presented as combining different physical studies namely, electromagnetic (EM) propagation, thermal diffusion and non-linear materials using a numerical algorithm. The algorithm was developed based on the two dimensional (2D) numerical transmission line method (TLM). The algorithm was applied to several practical examples namely, to model the electro-thermal analysis and the temperature development in a plasmonic nano-heat sources for terahertz applications; to predict the shape and the location of an arc discharge channel caused by a lightning strike using electro-thermal analysis, and to model diverter strips for lightning protection on aeroplanes. Different electro-thermal coupling approaches, such as fully and partially coupled methods were used to investigate the efficiency and accuracy of the model. In the fully coupled method the thermal model was allowed to change the electrical properties of materials in the electromagnetic model. On the other hand partial coupling did not consider the temperature dependency of the electrical properties in the electromagnetics model. Both of the models used the dissipated power from the electromagnetic model as a source signal to evaluate the temperature profile in the thermal model. Also different coupling interval timesteps were investigated to minimize the computational power needed without affecting the model accuracy.